Effects of different protocols of hydration on cardiorespiratory parameters during exercise and recovery - Vanderlei, Franciele Marques; Moreno, Isadora Lessa; Vanderlei, Luiz Carlos Marques [UNESP]; Pastre, Carlos Marcelo [UNESP]; De Abreu, Luiz Carlos; Ferreira, Celso (Springer Nature, 2013)
Abstract. Introduction. Hydration plays a key role in the physiological maintenance required by exercise. Objective. To evaluate the behavior of heart rate (HR), systolic (SBP) and diastolic (DBP) blood pressure, pulse oxygen saturation (SpO2) and respiratory rate (RR) of young people during and after prolonged physical exercise, with and without the intake of water or isotonic solution. Method. 31 young individuals (21.63 ± 1.86 years) were subjected to a four-step protocol with a 48-hour interval between each step, namely: i) a test to determine the incremental load used in subsequent steps, ii) a control protocol without hydration (CP), iii) an experimental protocol with water intake (PE1), iv) an experimental protocol with ingestion of isotonic (PE2). The protocols consisted of 10 min rest, 90 min of exercise on a treadmill at 60% of VO2peak and 60 min of recovery. The parameters HR, SBP, DBP, RR and SPO2 were measured at rest, at 30, 60 and 90 min of exercise, with the exception of RR; and at 1, 3, 5, 7, 10, 20, 30, 40, 50 and 60 min of recovery. The two-factor analysis of variance for repeated measures model was used for analysis (p<0.05). Results: There was a moment effect for all variables in exercise (p<0.001), however, no effect was observed between the protocols (SBP, p=0.998; DBP, p=0.897; SpO2, p=0.077, HR=0.281) and in the interaction moment and protocol (SBP, p=0.058; DBP, p=0.191 and SpO2, p=0.510, HR=0.496). In recovery there was also a moment effect for all variables analyzed (p<0.001). There was no effect among protocols for SBP (p=0.986), DBP (p=0.536) and RR (p=0.539), however in the SpO2 (p=0.001) and HR (p=0.033) variables, effects were observed between the protocols. Regarding the moment and protocol interaction, an effect was observed for HR (SBP, p=0.431; DBP, p=0.086; SpO2, p=0.445, RR, p=0.147, HR, p=0.022). Conclusion: For the type of exercise performed, both the water and the isotonic solution influenced the behavior of cardiorespiratory parameters, and independent of the type of hydration given the behavior of the parameters studied was similar. © 2013 Vanderlei et al.; licensee BioMed Central Ltd.
Keywords: Aerobic exercise; Blood pressure; Heart rate; Rehydration solutions; Respiratory rate